All About the Giants: Probing the Influences on Growth and Income Inequality at the End of the 20th Century - Albert Berry; John Serieux (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper presents estimates of world output growth from 1970 to 2000, the distribution of income among countries and persons for the years 1980, 1990 and 2000, and world poverty rates for the same years. It also presents the results of a series of simulation exercises that attempt isolate the effect of particular country and regional experiences on world output growth and changes in global income inequality and poverty. The authors find that rapid growth in China (despite a downward adjustment of official growth estimates) had a powerful impact on the growth of world output in both the 1980s and 1990s, but that negative economic growth in Eastern Europe more than offset that effect in the 1990s. With respect to the distribution of income however, the equalizing effect of China's rapid growth, despite the contradictory impact of increasing domestic inequality, was dominant through both the 1980s and 1990s. Only India's influence remained substantial by comparison. Other identifiable events of the period, such as the economic contraction in Eastern Europe and continued economic decline in Africa had little statistical impact. Thus, when the combined influence of these two countries' above-average growth rates is removed, the improving global distribution of income suggested by all statistical measures becomes one of sharply worsening inequality. The impact of these twocountries is similarly critical with respect to global poverty reduction.
Keywords: 330